Parenting Trends in the Digital Era: A Bibliometric Analysis from an Islamic Perspective in Muslim-Majority Societies - Arifurrohman Arifurrohman; Prima Cristi Crismono; Muhammad Ilyas (JURNAL AT-TURAS, 2025)
This study analyzes global parenting trends from an Islamic perspective using a bibliometric approach to explore digital parenting, emotion regulation, and parental stress in the modern technological era. Data were collected from the Scopus database, including peer-reviewed articles published between 2010 and 2023. Bibliometric analysis was conducted using VOSviewer to map citation patterns, keyword relationships, and geographic distribution of publications. The results indicate that parenting research is still predominantly dominated by Western countries, focusing mainly on psychological and social aspects without considering the spiritual dimension. In the Islamic context, parenting not only addresses the emotional and physical needs of children but also aims to instill the values of monotheism and noble morals. Islamic digital parenting emphasizes the importance of parental supervision and guidance to ensure technology use aligns with Islamic values. Emotion regulation teaches patience, compassion, and effective communication based on the Qur’an and Hadith, while parental stress can be managed through the concepts of tawakal (trust in God), dhikr (remembrance), and support from religious communities. This bibliometric study reveals a significant gap in research on Islamic parenting, particularly concerning the integration of Islamic teachings with the challenges of parenting in the digital age. Therefore, this study recommends developing a structured framework for Islamic digital parenting and identifying priority areas for future empirical research. Furthermore, the findings can inform the development of policies and parenting education curricula grounded in Islamic values to support Muslim families in navigating contemporary challenges.